2012
DOI: 10.1016/j.jacc.2012.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is associated with increased risk for stroke and systemic embolism. There is plausible evidence linking inflammation to the initiation and perpetuation of AF and AF-related thrombosis. Various inflammatory markers (C-reactive protein, tumor necrosis factor-α, interleukin-2, interleukin-6, and interleukin-8) have been associated with AF. Proposed mechanisms linking inflammation and the prothrombotic AF state include endothelial activation/damage, production of tissue factor from monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
562
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 713 publications
(596 citation statements)
references
References 42 publications
19
562
0
15
Order By: Relevance
“…Fifth, inflammatory reaction and prothrombotic state may produce LA thrombus. 23,24) However, inflammatory changes of LA endothelium and markers of coagulation were not evaluated in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Fifth, inflammatory reaction and prothrombotic state may produce LA thrombus. 23,24) However, inflammatory changes of LA endothelium and markers of coagulation were not evaluated in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Height, weight, and body fat predispose to LA enlargement, which in turn predisposes to AF 35, 36. Higher BMI is associated with inflammation, which is reflected in higher concentrations of C‐reactive protein 37. In addition, general obesity is a major risk factor for obstructive sleep apnea; sleep apnea predisposes to AF 30.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the joint association of elevated GGT and CRP levels was associated with a stronger risk of SCD, but the estimate was imprecise and was not statistically significant because of the small number of SCDs in each category (data not shown). Other likely pathways include the involvement of GGT in impairing antioxidant defense systems and promoting oxidative stress16 and underlying fatty liver,16 which is also associated with insulin resistance and oxidative stress,33, 34 all known to be associated with increased risk of CVD 35, 36, 37. Through its involvement in atheromatous plaque formation,29, 30 GGT may also cause acute myocardial ischemia, which is the most common trigger for fatal arrhythmias 38.…”
Section: Discussionmentioning
confidence: 99%